Growth Performance of Quails (Coturnix coturnix) Fed on Diets Containing Either Animal or Vegetable Protein Sources - Dahouda , M.; Adjolohoun, S.; Montchowui, E.H.; M. Senou, M.; Hounsou, N.M.D.; Amoussa, S.; Vidjannagni, D.S.; Abou, M.; Toleba, S.S. (International Journal of Poultry Science, 2013)
This study aimed at comparing two proteins sources on the performance of quail bred in Benin. Six groups of 45 quails from common breed, without sex discrimination, received diets containing either soybean meal (20 and 25%), fishmeal (20 and 25%), or their mixture (20 and 25%). The feeding period lasted six weeks. Quail weights were similar at the onset of experimentation but important variations according to feed were observed from the second week. At the end of fattening, the effect of the protein source on growth was noticed in favor of animals fed on soybean meal. The quail fed on soybean meal based diets showed higher weights compared to those which received fish flour diets. The mixture of both protein sources at 25% was more interesting than the mixture at 20%. The animals performance (Weight, DWG and FCR) were the lowest with fishmeal diet, suggesting the low quality of this protein source largely utilized as animal feed in Benin. Our results suggest that soyabean meal represents the best source of protein for quails and its optimal incorporation level in their diet is 20%.